Changes in pediatric sports injury presentation during the COVID-19 pandemic. A multicenter analysis - Johnson, M. A.; Halloran, K.; Carpenter, C.; Pascual-Leone, N.; Parambath, A.; Sharma, J.; Seltzer, R.; Ellis, H. B.; Shea, K. G.; Ganley, T. J. (Orthopaedic Journal of Sports Medicine, 2021)
Background: The current coronavirus 2019 (COVID-19) pandemic has prompted a multitude of public health response measures including social distancing, school cancellations, and cessation of organized sports. Purpose: To examine the impact of COVID-19 and corresponding public health measures on the characteristics of common pediatric musculoskeletal injuries associated with sports. Study Design: Cohort study; Level of evidence, 3. Methods:This was a multicenter retrospective cohort study comparing patients with sports injuries presenting to 3 geographicallydiverse level I pediatric trauma hospitals and outpatient orthopaedic surgery clinics in the United States during the COVID-19 pandemic and a prepandemic period at the same institutions. Patients were included if they presented for care between February15 and July 15 in 2020 (pandemic cohort) or between March 15 and April 15 in 2018 and 2019 (prepandemic cohort). Results: Included were 1455 patients with an average age of 12.1±4.5 years. When comparing patients presenting in 2018 and2019 with those presenting in 2020, we observed a decrease in mean age during the pandemic (12.6±4.0 vs 11.0±5.2 years;P¼.048). Additionally, a decrease in the proportion of injuries attributed to sports (48.8% vs 33.3%;P<.001) and those occurring atschool (11.9% vs 4.0%;P¼.001) was observed. The proportion of injuries attributable to clavicle fractures increased during theearly stages of the pandemic (13.2% vs 34.7%;P<.001). There was no statistically significant delay to care in injuries presentingduring the pandemic (41.5±141.2 vs 19.23±79.1 days;P¼.175). Conclusion: Across 3 tertiary care institutions, patients were seen without significant delay during the pandemic. We observed asignificant decline in pediatric musculoskeletal injuries associated with sports during the COVID-19 pandemic. This decrease hasbeen accompanied by a shift in both injury type and mechanism.